Stress and Motivation to Smoke among Adolescents - Firdaus, Insanul; Arnas Suwarni, Anggita; Agung Yudhianto, Kresna; Mei Astuti, Andriani; Witriyani, Witriyani (LPPM Universitas Duta Bangsa Surakarta, 2024)
Background: Stress is a condition of anxiety or mental strain brought on by challenging circumstances and motivates us to face obstacles and dangers in life. Stress often experienced by adolescents, with a reported high prevalence of depression among teenagers. Each person uses different stress coping techniques, some of which are beneficial and others of which are detrimental. Smoking is one of the negative stress coping strategies that some people turn to in the hopes of finding mental calm. However, smoking behavior is dangerous for both active and passive smokers, who may experience a range of illnesses, including cancer, lung disease, impotence, reproductive abnormalities, stroke, and possibly fatal pregnancy issues for the fetus. Objective: The aim of this research is to determine the relationship between stress levels and smoking motivation among adolescents. Method: This research is a quantitative descriptive study with a cross-sectional approach by involving 80 subjects of adolescents. The research instrument used a questionnaire that had been tested for validity. Analysis of this research data used the Spearman Rho test. Results: It was discovered that 38 subject (47.5%) had low level of stress, 26 subject (32.5%) had moderate levels of stress, 9 (11,25%) had high levels of stress, 7 (8,75%) had very high levels of stress. Smoking motivation was discovered that 59 subject (73.75%) had moderate smoking motivation, 31 subject (38.75%) had high smoking motivation. Conclusion: There is a relation between stress levels and smoking motivation among adolescents with a significance value of 0.00 (p<0.05).